Immunohistochemical features of the structure of fetuses’ uterus with a gestational term of 21-28 weeks from mothers, whose pregnancy is complicated by chronic infection of the lower genital tract - Polyasnyi, V. O.; Kupriianova, L. S. (Journal of Education, Health and Sport, 2021)
The relevance of the following article is prescribed by the growing number of perinatal mortality and morbidity among newborns due to the mother’s chronic infection of the lower genital tract (HILGT). It is commonly known, that HILGT contributes to the delay of the fetal development likewise is often manifested by the violation of internal organs and systems implementation. One of the most acute topic is the the fetus’ reproductive system in ther early gestation terms. However, the immunohistochemical features of the fetuses’ uterus structure with the gestational term of 21-28 weeks from mothers with HILGT on the current stage of the medical science develpment have not been described yet. The aim of the current research is to identify immunohistochemical features of the fetuses’ uterus structure with the term of gestation of 21-28 weeks from mothers, whose pregnancy is complicated by HILGT. Material of the research: 25 fetuses from mothers, whose course of pregnancy was physiological (group of comparison) as well as 25 fetuses from mothers, whose pregnancy was complicated by HILGT (main group). All fetuses had died intranatally, as a result of acute uterine placental and placental-fetal circulation. Research methods: organometric, histological, immunohistochemical, morphometric, statistical. The research results and their discussion: the organometric parameters of the fetuses’ uterus from the main group were clearily decreased in comparison to such parameters in case of the group of comparison. The decrease of the parameter of the uterine wall thickness of fetuses from mothers with the complicated pregnancy prescribes thinning of the main structural components. Namely: endometrium, myometrium and perimetrium. In case of endometrium of fetuses’ uterus a decrease of number of glands and the lack of their functional activity was noticed. It characterizes this layer as structurally immature. At the same time, in case of fetal organs of fetuses from mothers with complicated pregnancies, we could notice an increase in the number of apoptotically altered cells. Comparing to the structure of layers of uterine walls in case of fetuses from mothers with physiological pregnancy, in the uterus of fetuses from mothers with complicated pregnancy our attention is attracted by a massive growth of the connective tissue. In the myometrium it contributes to the disruption of the muscle fibers strusture likewise to its absence in some areas. By the immunohistochemical method it was possible to reveal a prevalence of the collagen of the III type in the structure of connective tissue likewise in the walls of blood vessels. It is connected primarily with disruption of the collagen’ maturation. The vascular component of the uterine wall in case of fetuses from mothers with HILGT differs from ones in case of fetuses from mothers with physiological pregnancy. This difference is grounded on the increase of endothelin-producing activity by vessels of both arterial and venous types. By processing preparations by monoclonal antibodies to estrogen, it has been postulated, that the intensity of the reaction as well as number of cells in the fetuses’ organs of the main group are clearily decreased comparing to ones in cases of fetuses from the group of comparison. The disorders of the fetuses’ uterus in case of fetuses from mothers with HILGT, that were provided in the current article, are prescribed by chronic hypoxia, endocrine disorders as well as influences of the infectious agents, that are taking place in case of such pathology. The characteristic features of the fetuses’ uterus structure in case of fetuses from mothers, whose pregnancy is complicated by HILGT, indicate gross violation in the organ’s implementation on the early stages of the fetal organogenesis, likewise they could be a leading link of pathogenesis of primary infertility’ development in the future ontogenesis.